Changes in the apparent quantum efficiency for photolysis of Hb(CO)1. - Zahroon, I A (1989)
Recent studies suggest that the allosteric state of the protein surrounding the hemes in hemoglobin affects both geminate recombination of CO and the apparent quantum efficiency (AQE) for photolysis (Rohlfs, R.J., J.S. Olson, and Q.H. Gibson, 1988, J. Biol. Chem. 263: 1803-1813. We report combined flow/flash experiments in which the AQE for photolysis of Hb(CO)1 was measured as a function of time delay after its formation. Experiments were carried out at 20 degrees C in 0.1 M phosphate buffer at pH 7.0 with CO saturations of 10% or less. The AQE was observed to decrease from a value close to 1.0 at short times to approximately 0.6 after 2 s. The fundamental photolysis step for carboxyhemoglobin is known to have a quantum efficiency of nearly 1.0, whereas the lower AQE values we observe result from competition between rapid geminate recombination and a rapid reaction step leading to escape of the CO to the solution phase. Changes in AQE values reflect changes in these rapid reaction steps which presumably result from conformational change in Hb(CO)1. The change in AQE is consistent with conversion of one or more hemes to an R-like state but these changes could not be even approximately described in terms of a simple two-state allosteric model.